The Influence of E-Service Quality and Product Quality on Customer Satisfaction: A Study of Perumdam Mojopahit Mojokerto Customers - Dita Nur Afifah; Mohammad Mas’ud Said; Ainul Chanafi (Review of Human Resources, Organizational Change, and Economic Impact, 2025)
This research pursues three central aims: determining the separate effect of E-Service Quality on consumer satisfaction, ascertaining the separate effect of Product Quality on the same outcome, and evaluating the combined influence of both variables on satisfaction among Perumdam Mojopahit Mojokerto’s patrons. The study adopted a quantitative framework with an associative orientation. Data collection involved the administration of survey instruments to a sample of one hundred customers drawn from the utility’s user base. Data analysis proceeded with partial testing using t-tests and simultaneous testing using F-tests. Results show that E-Service Quality positively and significantly affects satisfaction, supported by a t-statistic of 11.851 against the critical value of 1.985. Similarly, Product Quality demonstrates a favorable and meaningful effect, with a computed t-value of 3.849 against the same threshold. The associated p-value for these relationships registered at 0.000, falling well below the 0.05 significance level. The computed F-statistic of 60.805 further surpassed the tabulated F-value of 3.09. E-Service and Product Quality jointly account for 54.7% of the variance in customer satisfaction per the coefficient of determination, with the remainder explained by other factors not included in the model.